21st Century Technology Literacy in EFL Textbook: A Need Analysis - Akromi, Elok Nur Affah Al; Fitriyanti, Elvira (Interdisciplinary Social Studies, 2023)
Background: Despite living in the modern era, the level of Indonesian students’ technology literacy is still low, especially in the stage of junior high school. Aim: This research attempts to investigate what 21st century English as Foreign Language (EFL) textbook need in order to develop students’ technology literacy since the book is the most recognized medium for learning and being technology literate will also help students learn English better. Method: The textbook chosen for this research is the one published by the Ministry of Education, When English Rings a Bell, for grade 8 of junior high school. As for the data, they were taken from every chapter’s directions. They were analysed by implementing content analysis to detect the presence of technology literacy indicators in the textbook’s directions. Findings: Based on the results of the analysis, EFL textbook directions need the author’s initiative to modify them so that they can fit the ICT development indicators by adding more sentences related to applying presentation software usage and sharing information through online platforms. It is because the more literate the students in operating, accessing, managing, integrating, and evaluating modern technologies, especially ICT, the bigger their chances become in learning English successfully.